A Determinant Model of Digipreneurship Creativity in Coastal Areas to Support the Blue Economy - Fani, Lastri Anggi; Haryadi, Teddy; Novia, Siti Arita (SAFE-Network, 2025)
The rapid development of the digital economy has created new opportunities for the growth of digipreneurship in coastal regions. However, the level of creativity among coastal digital entrepreneurs remains highly diverse, particularly in areas where digital literacy, technological access, and socio-cultural dynamics differ significantly from urban centers. This study aims to identify the determinant factors influencing digipreneurship creativity that contribute to the development of a sustainable blue economy in coastal communities. Using a qualitative descriptive approach, data were collected from three active coastal digital entrepreneurs in Tanjungpinang: Nutribites (a healthy food based digipreneur), Sedap Laris (a home based food business), and ADS (Arus Digital Sinergi), a local software house dedicated to empowering digital entrepreneurs through innovative technological solutions. Data were gathered through open-ended interviews and analyzed using NVivo 14, utilizing coding, word frequency, and thematic mapping. The findings reveal four key determinants of creativity in coastal digipreneurship digital literacy and platform mastery, intrinsic motivation and personal value orientation, collaborative leadership and community engagement, and an innovative socio-cultural environment shaped by coastal traditions and digital market demands. NVivo visualizations (Word Cloud and thematic coding) highlight dominant keywords such as digital, content, creativity, coastal, customers, and promotion, indicating the importance of digital innovation and cultural identity in shaping creative business practices. The study concludes that creativity in coastal digipreneurship emerges from the interaction between individual capabilities and community-based digital ecosystems. Strengthening digital skills, enhancing community collaboration, and integrating local cultural elements can significantly improve the sustainability of the coastal blue economy.